2012
DOI: 10.1074/jbc.m111.303701
|View full text |Cite
|
Sign up to set email alerts
|

Target of Rapamycin Complex 2 Signals to Downstream Effector Yeast Protein Kinase 2 (Ypk2) through Adheres-Voraciously-to-Target-of-Rapamycin-2 Protein 1 (Avo1) in Saccharomyces cerevisiae

Abstract: Background: Molecular mechanisms underlying target of rapamycin complex 2 (TORC2) signaling are poorly understood. Results: The TORC2 component Avo1 directly interacts with a downstream substrate Ypk2. Conclusion: Avo1-Ypk2 interaction is essential for TORC2-Ypk2 coupling and activation of the downstream effector pathway(s) regulating cell integrity and actin organization. Significance: Physical associations between TORC2 components and specific downstream effectors provide the molecular basis for selective do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 44 publications
1
19
0
1
Order By: Relevance
“…Previous work has suggested that Avo1 also plays a role in substrate recruitment (Liao and Chen, 2012;Liu et al, 2013;Lu et al, 2011). Specifically, residues 600-840 of Avo1 were shown to bind to the central portion of Ypk2 (Liao and Chen, 2012). This is the same region of Avo1 that displayed multiple crosslinks with Lst8 ( Figures 3A and 3B).…”
Section: Subunit Organization In the Torc2 Protomer And Implications mentioning
confidence: 86%
See 2 more Smart Citations
“…Previous work has suggested that Avo1 also plays a role in substrate recruitment (Liao and Chen, 2012;Liu et al, 2013;Lu et al, 2011). Specifically, residues 600-840 of Avo1 were shown to bind to the central portion of Ypk2 (Liao and Chen, 2012). This is the same region of Avo1 that displayed multiple crosslinks with Lst8 ( Figures 3A and 3B).…”
Section: Subunit Organization In the Torc2 Protomer And Implications mentioning
confidence: 86%
“…Our localization of the Tor2 kinase domain further implies that the ATP-and substrate-binding sites are accessible from the lateral-dorsal part of the structure next to the thumb comprising Avo1 ( Figure 5D, Figure 6). Previous work has suggested that Avo1 also plays a role in substrate recruitment (Liao and Chen, 2012;Liu et al, 2013;Lu et al, 2011). Specifically, residues 600-840 of Avo1 were shown to bind to the central portion of Ypk2 (Liao and Chen, 2012).…”
Section: Subunit Organization In the Torc2 Protomer And Implications mentioning
confidence: 98%
See 1 more Smart Citation
“…It has been reported that membrane stress caused by inhibition of sphingolipid synthesis or membrane stretch (induced by hypotonic shock) causes two PH domain-containing proteins (Slm1 and Slm2) to relocalize from eisosomes to a separate PM region that contains TORC2 and leads to increased TORC2 activation of Ypk1 and Ypk2 (Berchtold et al, 2012), purportedly because Slm1 and Slm2 recruit Ypk1 and Ypk2 to TORC2 (Niles et al, 2012). However, other evidence indicates that Avo1 (ortholog in other organisms is Sin1) is the subunit of the TORC2 complex primarily responsible for substrate recognition of Ypk1 and its orthologs, including association of S. cerevisiae Ypk2 with Avo1 (Liao and Chen, 2012), Gad8 with Sin1 in fission yeast (Ikeda et al, 2008; Kataoka et al, 2014), and SGK1 with mSin1 in mammalian cells (Jacinto et al, 2006; Yang et al, 2006; Lu et al, 2011; Liu et al, 2013). Regardless of the actual mechanism by which the activity of the TORC2-Ypk1 signaling module is affected by these assaults on the PM, it clearly sets in motion processes that allow the cells to cope appropriately with these stresses.…”
Section: Introductionmentioning
confidence: 99%
“…At the C-terminal region of Avo1, an essential PH (Pleckstrin homology)-like domain exists, through which TORC2 may tether to the definite region of the plasma membrane called the MCT (membrane compartmentcontaining TORC2) [72]. The CRIM (conserved region in the middle) domain exists in proximity to the N-terminal side of RBD and has been implicated in binding to the substrates of TORC2 [73,74]. Avo1 binds to the kinase domain of Tor2 via Lst8 [25].…”
Section: Subunit Componentsmentioning
confidence: 99%